Extended Exposure of Gallium Nitride Heterostructure Devices to a Simulated Venus Environment - Eisner, Savannah R.; Alpert, Hannah S.; Chapin, Caitlin A.; Yalamarthy, Ananth Saran; Satterthwaite, Peter F.; Nasiri, Ardalan; Port, Sara; Ang, Simon; Senesky, Debbie G. (2021 IEEE Aerospace Conference (50100), 2021)
Further development of harsh environment electronics capable of uncooled operation under Venus surface atmospheric conditions (~460°C, ~92 bar, corrosive) would enable future missions to the surface of Venus to operate for up to a year. Wide band-gap gallium nitride (GaN) heterostructure devices are attractive candidates for Venus lander missions due to their ability to withstand high-temperature exposure. Here, we present the first assessment of the electrical integrity of GaN-based devices subject to Venus surface atmospheric conditions. Three unique device architectures were fabricated at the Stanford Nanofabrication Facility and exposed in a Venus simulation chamber for 244 hours at the University of Arkansas Center for Space and Planetary Sciences. The three device architectures tested were InAlN/GaN high electron mobility transistors (HEMTs), InAlN/GaN Hall-effect sensors, and AlGaN/GaN UV photo detectors, which all have potential applications in the collection and readout of sensor data from Venusian landers. After exposure, HEMT threshold voltage had shifted only ~1% and gate leakage current remained on the same order of magnitude, demonstrating stability of the IrOx gate under supercritical CO2 ambient. Fluctuations in drain current after exposure are attributed to thermal detrapping and electrically-activated trapping processes. Measurements of the InAlN/GaN 2DEG properties in virgin and exposed Hall-effect sensors were comparable. Furthermore, the Hall-effect sensors exhibited a maximum change of only +11.4% in current-scaled sensitivity and −6.6% in voltage-scaled sensitivity post-exposure. The UV photodetectors with 362 nm peak wavelength exhibited an average decrease in responsivity of 38% after exposure, which is thought to be due to strain relaxation or ohmic contact degradation. Similar performance of the InAlN/GaN HEMTs and Hall-effect sensors before and after exposure highlights the viability of this material platform for development of Venus surface electronics, while the decrease in AlGaN/GaN UV photocurrent requires further analysis to assess whether the AlGaN/Ga heterostructure is suitable for robust, Venus-capable electronics.